2015
DOI: 10.1097/mca.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of second-generation drug-eluting stents for coronary artery disease, everolimus-eluting versus zotarolimus-eluting stents

Abstract: The new-generation Resolute-ZES and EES have a similar long-term safety and efficacy profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A meta-analysis [4] comparing the long-term effect of second generation DES for coronary artery disease, published by Li et al, showed ZES and EES to be associated with a similar efficacy and safety profile. EES did not reduce the rate of ST defined by the ARC with OR: 0.83, 95% CI: 0.56 – 0.25; P = 0.37.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis [4] comparing the long-term effect of second generation DES for coronary artery disease, published by Li et al, showed ZES and EES to be associated with a similar efficacy and safety profile. EES did not reduce the rate of ST defined by the ARC with OR: 0.83, 95% CI: 0.56 – 0.25; P = 0.37.…”
Section: Discussionmentioning
confidence: 99%
“…However, ST in patients treated with Zotarolimus Eluting Stents (ZES) and EES have seldom been analyzed using a large number of randomized patients. Previously published meta-analyses which focused mainly on the general adverse clinical outcomes associated with ZES and EES, did not specifically focus on the different types of ST following PCI [4, 5]. Hence, this current analysis aimed to compare ST associated with ZES versus EES at 1 year follow up, using a large number of patients extracted from randomized trials.…”
Section: Introductionmentioning
confidence: 99%